2011
DOI: 10.1002/em.20647
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring of rural workers exposed to a complex mixture of pesticides in the municipalities of Tianguá and Ubajara (Ceará state, Brazil): Genotoxic and cytogenetic studies

Abstract: In recent years, the use of pesticides in agriculture has been steadily increasing, and associations between exposure to agricultural chemicals and DNA damage and cancer have been reported. Brazil is one of the world leaders in pesticide use; however, studies that evaluate the impact of pesticide exposure on cancer incidence and mortality are very scarce in the Brazilian population. The alkaline comet assay and the chromosome aberration (CA) test were used to evaluate primary DNA damage in the peripheral blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 56 publications
6
7
0
Order By: Relevance
“…Exposed workers presented significantly longer comet tail lengths in exfoliated buccal cells than the non-exposed individuals. Our results agree with those of other authors who have used the comet assay in human lymphocytes to evaluate DNA damage in the biomonitoring of populations occupationally exposed to pesticides and it has demonstrated positive results (Garaj-Vrhovac and Zeljezic 2000Zeljezic and Garaj-Vrhovac 2001;Ünderğer and Başaran 2002;Grover et al 2003;Ascarrunz et al 2006;Castillo-Cadena et al 2006;Remor et al 2009;Paiva et al 2011;Wilhelm et al 2015).…”
Section: Discussionsupporting
confidence: 95%
“…Exposed workers presented significantly longer comet tail lengths in exfoliated buccal cells than the non-exposed individuals. Our results agree with those of other authors who have used the comet assay in human lymphocytes to evaluate DNA damage in the biomonitoring of populations occupationally exposed to pesticides and it has demonstrated positive results (Garaj-Vrhovac and Zeljezic 2000Zeljezic and Garaj-Vrhovac 2001;Ünderğer and Başaran 2002;Grover et al 2003;Ascarrunz et al 2006;Castillo-Cadena et al 2006;Remor et al 2009;Paiva et al 2011;Wilhelm et al 2015).…”
Section: Discussionsupporting
confidence: 95%
“…This study demonstrates a significant genotoxic effect in DNA damage (Comet assay) and mutagenic effect (CBMN assay) during pesticides application, which is consistent with others reports [26,[34][35][36]. Pesticide sprayers are the most frequently exposed group of agricultural workers, with positive findings obtained in 18 of 27 studies, presenting 1.12-7.67 higher exposure rates than other workers [3].…”
Section: Discussionsupporting
confidence: 94%
“…The Comet assay has been used to determine the extent of DNA damage in the lymphocytes of farm workers with occupational exposure to a complex mixture of pesticides [34][35][36]. In relation to the cytokinesis-block micronucleus (CBMN) assay, used to measure micronuclei (MN), nucleoplasmic bridges (NPB) and nuclear buds (NBUD), higher frequency of NPB and MN were detected between the pesticide application and leaf harvest groups, and higher frequencies of NPB were obtained for the farmers.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, animal studies have recently reported that mixtures may have a greater effect than individual compounds alone. In one study of rats, no effects were seen for individual endocrine disrupting pesticides (EDPs) for particular endpoints like gestational age and mortality, while exposure to a mixture of the EDPs induced health effects on the same endpoints (Paiva et al, 2011). Another study showed that mixtures of compounds that act by disparate mechanisms of toxicity to disrupt complex signaling pathways result in cumulative effects, regardless of the mode of action of the individual components (Rider et al, 2010).…”
Section: Discussionmentioning
confidence: 99%